1997
DOI: 10.1063/1.556011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluated Kinetic, Photochemical and Heterogeneous Data for Atmospheric Chemistry: Supplement V.   IUPAC Subcommittee on Gas Kinetic Data Evaluation for Atmospheric Chemistry

Abstract: This paper updates and extends previous critical evaluations of the kinetics and photochemistry of gas-phase chemical reactions of neutral species involved in atmospheric chemistry [J. Phys. Chem. Ref. Data 9, 295 (1980); 11, 327 (1982); 13, 1259 (1984); 18, 881 (1989); 21, 1125 (1992)]. The work has been carried out by the authors under the auspices of the IUPAC Subcommittee on Gas Phase Kinetic Data Evaluation for Atmospheric Chemistry. Data sheets have been prepared for 658 thermal and photochemical reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
538
2
3

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 924 publications
(585 citation statements)
references
References 0 publications
42
538
2
3
Order By: Relevance
“…The NIST reaction data base (NIST standard reference data 17 version 7.0, web version public release 1.1) (NIST, 2000) was used to provide values of rate constants for the reactions of HO 2 and NO with organic peroxy radicals with which to determine the values of m and c. If more than one determination of a rate constant existed the IUPAC recommendation (2001 web version December 2001) based on evaluations (Atkinson et al, 1997a;Atkinson et al, 1997b;Atkinson et al, 1999;Atkinson et al, 2000;Atkinson et al, 1997c) was used, otherwise the values were simply averaged. The database presented here is considerably larger than the previous work.…”
Section: Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…The NIST reaction data base (NIST standard reference data 17 version 7.0, web version public release 1.1) (NIST, 2000) was used to provide values of rate constants for the reactions of HO 2 and NO with organic peroxy radicals with which to determine the values of m and c. If more than one determination of a rate constant existed the IUPAC recommendation (2001 web version December 2001) based on evaluations (Atkinson et al, 1997a;Atkinson et al, 1997b;Atkinson et al, 1999;Atkinson et al, 2000;Atkinson et al, 1997c) was used, otherwise the values were simply averaged. The database presented here is considerably larger than the previous work.…”
Section: Methodmentioning
confidence: 99%
“…Wallington et al, 1994) Note where the reference is given as IUPAC it refers to the IUPAC Subcommittee on Gas Kinetic Data Evaluation for Atmospheric Chemistry Dec 2001, which is based on the original references (Atkinson et al, 1997a;Atkinson et al, 1997b;Atkinson et al, 1999;Atkinson et al, 2000;Atkinson et al, 1997c). .…”
Section: Acknowledgementsmentioning
confidence: 99%
“…In addition, in their review, Atkinson et al [63] The reverse decomposition rate constants are calculated from microscopic reversibility. We assume that any C 8 H 17 Ȯ 2 radical, with 75 (3N-6) vibrational modes, is rapidly stabilized to its ground state, so the energy released during C-O bond formation is easily dissipated throughout the molecule.…”
Section: Reaction Type 10: ṙ ؉ O 2 Additionmentioning
confidence: 99%
“…By noting a coincidence between maxima in measured OH concentrations (as usual, this will be denoted by square brackets embracing the chemical species, in this case [OH]) and the ozone observations, they suggested that a good correspondence between the ozone production and destruction rates could be obtained if a downward revision in the rate constant of reaction 3 could be done. However, the proposed downward revision by 50 to 70% lacks support both from theoretical [11][12][13] and recommended 14 data while leading to large underestimates of the observed abundances 6 of OH and HO 2 . In turn, Sandor and Clancy 15 found that ground-based microwave measurements of HO 2 concentrations at 50-80 km altitudes were 23-47% higher than photochemical model values at mid day, agree with model values at 0900 local time, and exceed model mixing ratios by 70-100% immediately after sunset.…”
Section: Introductionmentioning
confidence: 99%
“…However, [H] is rather small up to 40 km reaching at 55-60 km the value of [OH] reported in the literature, 1 which attains its maximum value close to 65 km (see ref 9 and section 3.2 for a somewhat different representation). The y ) 0 and 1 mechanisms should therefore be considered together in the upper stratosphere and mesosphere (given the relatively small rate constant 14,33,34 of the HO 2 + O 3 reaction, we ignore at this stage the mechanism involving y ) 2).…”
Section: Novel Mechanismsmentioning
confidence: 99%